2018
DOI: 10.1088/1751-8121/aadd53
|View full text |Cite
|
Sign up to set email alerts
|

Crossover between diffusion-limited and reaction-limited regimes in the coagulation–diffusion process

Abstract: The change from the diffusion-limited to the reaction-limited cooperative behaviour in reaction–diffusion systems is analysed by comparing the universal long-time behaviour of the coagulation–diffusion process on a chain and on the Bethe lattice. On a chain, this model is exactly solvable through the empty-interval method. This method can be extended to the Bethe lattice, in the ben-Avraham–Glasser approximation. On the Bethe lattice, the analysis of the Laplace-transformed time-dependent particle-density is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…One could not complete a work on diffusion without a brief discussion of reaction-diffusion processes [185,[188][189][190]. Exactly solvable reaction-diffusion models consist largely of single species reactions in one dimension, e.g., variations of the coalescence process, A + A → A + S [191][192][193] and the annihilation process A + A → S + S [192,193], where A and S denote occupied and empty sites, respectively.…”
Section: Reaction-diffusion Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…One could not complete a work on diffusion without a brief discussion of reaction-diffusion processes [185,[188][189][190]. Exactly solvable reaction-diffusion models consist largely of single species reactions in one dimension, e.g., variations of the coalescence process, A + A → A + S [191][192][193] and the annihilation process A + A → S + S [192,193], where A and S denote occupied and empty sites, respectively.…”
Section: Reaction-diffusion Processesmentioning
confidence: 99%
“…This is one of the rare cases where theoretical statistical mechanics can be compared with experiments and also shows that simple mean-field schemes are not enough. For an introduction see [188], and for up to date references see [190].…”
Section: Reaction-diffusion Processesmentioning
confidence: 99%
“…The Bethe lattice approach has been employed, among many other examples, for the analysis of the phase diagram of the Blume-Emery-Griffiths model [37], of modulated phases emerging in the Ising model with competing interactions [38], the Potts model [39], lattice models of glassy systems [40] and localisation transitions [41], as well as a phase behaviour of confined ionic liquids [42,43]. Bethe lattice approach was also used in the analytical studies of different diffusion-reaction processes [44][45][46], processes of random and cooperative sequential adsorption [47] or of the structural properties of branched polymers [48,49]. The accuracy of such an approximation has been recently accessed in the numerical analysis of the Blume-Capel model and it was shown that, somewhat surprisingly, it provides a very accurate estimate of the location of the demarkation curve between the ordered and disordered phases [50].…”
Section: Modelmentioning
confidence: 99%
“…The Bethe lattice approach has been employed, among many other examples, for the analysis of the phase diagram of the Blume-Emery-Griffiths model [37], of modulated phases emerging in the Ising model with competing interactions [38], the Potts model [39], lattice models of glassy systems [40] and localisation transitions [41], as well as a phase behaviour of confined ionic liquids [42,43]. Bethe lattice approach was also used in the analytical studies of different diffusion-reaction processes [44][45][46], processes of random and cooperative sequential adsorption [47] or of the structural properties of branched polymers [48,49]. The accuracy of such an approximation has been recently assessed in the numerical analysis of the Blume-Capel model and it was shown that, somewhat surprisingly, it provides a very accurate estimate of the location of the demarkation curve between the ordered and disordered phases [50].…”
Section: Modelmentioning
confidence: 99%